Rework and material waste due to change of electrical pipeline construction drawing of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding rework and material waste due to change of electrical pipeline construction drawing of BRAC University new campus project.